THE ACTIVITY OF PEDAGOGUE AND TEACHER: HISTORY AND CONTEMPORANEITY - Kudratova Umida Rahmatovna (Galaxy International Interdisciplinary Research Journal, 2021)
This article focuses on teacher performance in the modern education system. In historical reality, the activities of teachers, the duties of teachers, their role in the development of society are analyzed from a socio-philosophical point of view.